2023
DOI: 10.21203/rs.3.rs-3211477/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Socio-demographic Determinants of the Knowledge of Monkeypox Virus among the General Public: A Cross-Sectional Study in a Tertiary Care Center in Nepal

Santa Kumar Das,
Abhinav Bhattarai,
Kiran Paudel
et al.

Abstract: Background and Objective Monkeypox virus (MPXV) is the causative agent of monkeypox's zoonotic infection and was declared a global emergency by the World Health Organization (WHO). Studies from different countries have shown insufficient knowledge among the general public on MPXV. This study aimed to assess the knowledge of the general public of Nepal on MPXV. Methods Three hundred people were interviewed in person in October 2022, and 282 complete responses were recorded. The questionnaire related to the know… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
1
1
Order By: Relevance
“…Moreover, this finding was in contrast with the general population results in Nepal where 53.8% of the study participants had good knowledge; 70 in Saudi Arabia, 48% of the total participants had high knowledge; 71 in Nigeria, 58.7% had good knowledge; 72 in China, 56.5% had a high level of knowledge; 73 in Malaysia, 49.3% of medical students had good mpox knowledge; 74 in Bangladesh, 30.59% medical doctors had good knowledge; 35 55.3% of medical students from 27 low and high-income countries 75 and 26% global healthcare workers had good mpox knowledge. 44 Differences in the study setting, study period, perceptions about mpox infection, source of information, and taking of training could all be contributing factors to this discrepancy.…”
Section: Discussioncontrasting
confidence: 84%
“…Moreover, this finding was in contrast with the general population results in Nepal where 53.8% of the study participants had good knowledge; 70 in Saudi Arabia, 48% of the total participants had high knowledge; 71 in Nigeria, 58.7% had good knowledge; 72 in China, 56.5% had a high level of knowledge; 73 in Malaysia, 49.3% of medical students had good mpox knowledge; 74 in Bangladesh, 30.59% medical doctors had good knowledge; 35 55.3% of medical students from 27 low and high-income countries 75 and 26% global healthcare workers had good mpox knowledge. 44 Differences in the study setting, study period, perceptions about mpox infection, source of information, and taking of training could all be contributing factors to this discrepancy.…”
Section: Discussioncontrasting
confidence: 84%
“…Research has shown that a person’s socio-economic position, which includes factors like education, occupation, and income, can have a significant impact on their overall health (6). Typically, individuals with a lower socio-economic status are more susceptible to health issues and disease infection, hence, contributing to health inequities that impact individuals across all levels of society (1, 18).…”
Section: Introductionmentioning
confidence: 99%